2020
DOI: 10.1101/2020.03.12.985218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing a Coarse-Grained Model for Bacterial Cell Walls and Evaluating Mechanical Properties and Free Energy Barriers

Abstract: The bacterial cell envelope of Gram-negative bacteria is a complex biological barrier with multiple layers consisting of the inner membrane, periplasm of peptidoglycan and the outer membrane with lipopolysaccharides (LPS). With rising antimicrobial resistance there is increasing interest in understanding interactions of small molecules with the cell membrane to aid in the development of novel drug molecules. Hence suitable representations of the bacterial membrane are required to carry out meaningful molecular… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…In this study, the location of the two membranes was determined by using the full-length AcrAB-TolC RND pump as a guide, but the cell wall was omitted due to the lack of a CG model and paucity of details regarding the physiological location of the cell wall with respect to the protein. We note here that CG models of the E. coli cell wall have now been reported [14,15].…”
Section: Organisation Of the Cell Envelopementioning
confidence: 64%
“…In this study, the location of the two membranes was determined by using the full-length AcrAB-TolC RND pump as a guide, but the cell wall was omitted due to the lack of a CG model and paucity of details regarding the physiological location of the cell wall with respect to the protein. We note here that CG models of the E. coli cell wall have now been reported [14,15].…”
Section: Organisation Of the Cell Envelopementioning
confidence: 64%
“…To improve the efficacy and selectivity of AMPs, it is crucial to understand their interactions with different components of the bacterial cell envelope. In recent years several molecular dynamics simulations from our laboratory and others have shown that it is important to assess the barrier properties of PGN and OM which are physicochemically and mechanically distinct from the interaction with the bilayer environment of the IM [8][9][10][11][12]. Notably, the OM offers a heterogeneous barrier for antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in force-field development and increased computing power, molecular dynamics (MD) simulations have increasingly been used to study the barrier properties of the bacterial cell envelope. Insights into the barrier properties of the bacterial membranes have recently been obtained using free energy methods based on umbrella sampling and metadynamics [8, 10, 11, 15]. The amphiphilic nature of LPS acts as a barrier for both hydrophobic and hydrophilic molecules prohibiting their translocation across the bacterial cell envelope [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Therefore, the glycan strands in S. aureus are modelled with a hydroxyl ('OH') group attached to the anomeric carbon of a NAM residue at the terminal ends. While, following our previous work, 29 the strands in E. coli terminate with a methoxy ('OCH 3 ') group bonded with anomeric carbon of NAM. The model glycan strands are 8 disaccharide units long.…”
Section: Single Strands Of Peptidoglycansmentioning
confidence: 99%